Non-invasive methods of registration and analysis of biosignals - Dorosh, N.; Kuchmiy, H.; Ivanushkina, N.; Pushkarska, N. (Видавництво Львівської політехніки, 2010)
In this paper, the non-invasive methods of investigation of circulatory system and the results of photopletizmogram modeling are shown.
Keywords: photopletizmogram; spectral analysis